Nweleya dan nilai-nilai yang terkandung di dalamnya - Ratumanan, Tanwey Gerson; Untailawan, Victor; Marantika, Juliaans E. R.; Mattitaputty, Christi (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Nweleya or Weleya is a typical tradition of the people on Masela Island, Southwest Maluku Regency. It was marked by sharing food in one dish between the brothers in a traditional house. Eating together on one plate between friends, especially those who are bound by the Klaktuty tradition or the tradition of entrusting children to be breastfed by other mothers who are breastfeeding. However, due to the intrusion of building this tradition, it began to disappear from the community. Therefore the purpose of this study is as a basis for cultural exploration on Masela Island. This study uses a phenomenological approach with participant observation techniques. The results of the field study show that philosophically, this tradition has a very high value and shows the first value, togetherness, kinship, and inner bond as one brother's unit. Second, it has the same taste and taste, continuity in love, and pleasure. Third, it builds mutual respect for life, care, and sharing of resources. Finally, it produces patience and self-control of people on the island of Masela. Unfortunately, along with the development of modernization, traditional houses have been replaced with permanent and semi-permanent houses with new models that are different from traditional houses. This change had a serious impact on the erosion of the Nweleya tradition. Therefore, the tradition of eating dishes is rare and difficult to find in the villages of Masela Island.DOI: 10.17977/um022v5i12020p010